RECONSTRUCTING THE STRATEGIC PLAN OF ISLAMIC EDUCATIONAL INSTITUTIONS BASED ON COGNITIVE PSYCHOLOGY FOR ACCELERATING THE QUALITY OF LEARNING - Sri Inayati Ningrum; Jasiah Jasiah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
The quality of education in Islamic educational institutions has long been a focal point for enhancing both academic performance and the moral development of students. However, there is a growing need to address the cognitive aspects of learning in these institutions, which has often been overlooked in strategic planning. This research explores the integration of cognitive psychology into the strategic plans of Islamic educational institutions, aiming to accelerate the quality of learning through a more psychologically informed approach to education. The study’s purpose is to reconstruct the strategic planning process by incorporating principles from cognitive psychology, focusing on memory retention, motivation, and problem-solving. A qualitative approach with a descriptive design was employed, involving interviews, focus group discussions, and document analysis across 15 Islamic educational institutions. The findings reveal significant gaps in the integration of cognitive psychology, with universities showing better adoption of cognitive-based strategies compared to primary schools and madrasahs. Institutions that integrated cognitive psychology into their strategies demonstrated improved student engagement and academic performance. This research concludes that integrating cognitive psychology into the strategic planning of Islamic educational institutions can enhance learning outcomes, foster critical thinking, and improve student motivation. The study provides a framework for future educational leaders to incorporate cognitive psychology principles to optimize educational strategies.